Evaluasi User Experience Pada Sistem Informasi Perpustakaan Menggunakan User Experience Questionnaire - Rondonuwu, Yeremia Victor; Kurniawan, David Thanlian (Journal of Information System Research (JOSH), 2024)
This study evaluates the User Experience (UX) of the Library Information System at Pignatelli Triputra University using the User Experience Questionnaire (UEQ) to ensure that investment in the development of the library information system provides maximum benefits, minimizes user barriers, and enhances the effectiveness and efficiency of library operations. The study involved 30 students as respondents, measuring six components of user experience with average scores: attractiveness (1.61), clarity (1.84), accuracy (1.51), efficiency (1.88), stimulation (1.38), and novelty (0.88). The results indicate that clarity has the highest score, while novelty has the lowest, indicating the need for improvement in this area. The average scores for attractiveness, efficiency, and stimulation fall into the "Good" category, while novelty is only "Above Average." The findings of this study suggest that enhancing the "novelty" aspect of the library information system is a critical recommendation for the Library and IT Division at Pignatelli Triputra University in the information system upgrading process. This study is also expected to serve as a reference for other educational institutions in developing more efficient and user-friendly library information systems to improve user satisfaction and operational effectiveness.